Pregnancy in a Woman with Untreated Vesico-Cloacal Extrophy: A Clinical Case - M’betid-Degana, Roch; Kossa-Ko-Ouakoua, Gilles-Davy; M’betid-Degana, Geniva Gracelia Vanciane; Kossa Yamenda, Hilary Mattie; Doui-Doumgba, Antoine (European Scientific Journal, ESJ, 2026)
Introduction : Congenital malformations in a woman carrying a pregnancy are extremely rare. Report case : We report a case of a 16-year-old polymalformed woman with a pregnancy, referred from a rural health facility without a technical platform and qualified human resources (Batangafo District Hospital) to a facility with limited resources (Sino-Central African Friendship University Hospital Center in Bangui, the capital of the Central African Republic). The patient was successfully surgically managed: a caesarean section was performed, resulting in the cephalic extraction of a live newborn of sex female weighing 2,950 g with an Apgar score of 10/10 at the 1st, 5th and 10th minutes of life and the reconstructive surgery for various malformations. The post-operative period was simple and the patient was discharged on day 15. Conclusion : This case of multiple malformations during pregnancy remains an exceptional situation and highlights the need for prenatal monitoring, ultrasound evaluation, and multidisciplinary care.